TAKRORNING TARJIMADAGI XUSUSIYATLARI ERNEST XEMINGUEYNING “CHOL VA DENGIZ” ASARI MISOLIDA («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The art of translation is a complex interplay of linguistic, cultural and literary nuances in which each word has the potential to form the essence of the original work in a new language. Among the countless techniques used in translation, repetition stands out as a notable and often interesting element. Repetition, in its various forms, serves not only as a stylistic device, but also as a carrier of deeper meanings, nuances and emotions within the text. This article explores the complex area of repetition in the context of translation, with a particular focus on the famous work of Ernest Hemingway. With its sparse prose and profound themes, Hemingway's masterpiece provides a rich landscape for exploring the implications and challenges of translating repetition.
Keywords: stylistic elements, cultural adaptation, semantic equivalence, translation strategies, cultural identity, foundations of interpretation, literary analysis.